2006
DOI: 10.1037/0735-7036.120.2.79
|View full text |Cite
|
Sign up to set email alerts
|

Song Perception During the Sensitive Period of Song Learning in Zebra Finches (Taeniopygia guttata).

Abstract: The sensitive period is a special time for auditory learning in songbirds. However, little is known about perception and discrimination of song during this period of development. The authors used a go/no-go operant task to compare discrimination of conspecific song from reversed song in juvenile and adult zebra finches (Taeniopygia guttata), and to test for possible developmental changes in perception of syllable structure and syllable syntax. In Experiment 1, there were no age or sex differences in the abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
40
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 43 publications
12
40
0
Order By: Relevance
“…These results of overall sex similarity are comparable to findings from females and males in previous song discrimination experiments (Braaten and Reynolds 1999;Riebel et al 2002;Braaten et al 2006;Campbell and Hauber 2009c) indicating the shared importance and implying a shared ontogenetic pathway of song perception preference between the sexes. Consistent with optimal acceptance threshold theory (Reeve 1989; Fig.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results of overall sex similarity are comparable to findings from females and males in previous song discrimination experiments (Braaten and Reynolds 1999;Riebel et al 2002;Braaten et al 2006;Campbell and Hauber 2009c) indicating the shared importance and implying a shared ontogenetic pathway of song perception preference between the sexes. Consistent with optimal acceptance threshold theory (Reeve 1989; Fig.…”
Section: Discussionsupporting
confidence: 92%
“…In light of the vast sex differences in the neuroanatomical (Wade and Arnold 2004) and behavioural (Zann 1996) song systems of the Zebra Finch, we might have expected distinct responses between female and male subjects, but our findings were more consistent with previous research that has indicated a lack of sex effect in song discrimination playback experimentation (Braaten and Reynolds 1999;Riebel et al 2002;Braaten et al 2006;Hauber et al 2007b). The only behavioural measure of discrimination that presented a significant sex difference was the measure of spatial discrimination.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Songbirds, including juveniles, can be trained to discriminate among complex sounds and to demonstrate their perceptual preferences for sounds by approaching or eliciting the presentation of some sounds over others (Miller, 1979; Dent and Dooling, 2004; Braaten et al, 2006; Gess et al, 2011). Therefore, one can test for experience-dependent changes in perceptual skills over the course of postnatal development, and search for neural coding correlates (Grace et al, 2003; Woolley et al, 2005; Hauber et al, 2007; Phan and Vicario, 2006; Woolley et al, 2010; Schneider and Woolley, 2010).…”
Section: Developmental Plasticity Of Central Auditory Computationsmentioning
confidence: 99%
“…Both birds learn their vocalizations, but budgerigars continue to modify those vocalizations throughout their lives, while zebra finches generally learn one song as juveniles and continue to use that song throughout their life (e.g., Tchernichovski et al, 2001). Zebra finches can place song notes into categories (Sturdy et al, 1999(Sturdy et al, , 2001, and a recent study by Braaten et al (2006) showed that adult and juvenile zebra finches can also properly categorize songs versus reversed songs.…”
Section: E-mail Address: Mdent@buffaloedu (Ml Dent)mentioning
confidence: 99%